Direct Utilization of Dry Goat Manure as Base Fertilizer on Dry Land for Eggplant Plants in Majene Regency - Ilham, Ilham; Yanti, Nur Aida; Novitasari, Ervi; Rahman, Khaidir; Utami, Rahmawati Ning (ITScience (Information Technology and Science), 2025)
Majene Regency, West Sulawesi, is a region with dry agro-climate characteristics that are challenging for the growth of horticultural crops such as eggplant. The decline in eggplant productivity in West Sulawesi is suspected to be due to dependence on synthetic chemical fertilizers that damage soil structure and are not adaptive to dry land conditions. Based on sustainable agriculture theory, dry goat manure is considered an alternative organic fertilizer rich in macronutrients and granular texture that supports soil aeration and drainage. This study aims to assess the effectiveness of direct use of dry goat manure as a base fertilizer to increase eggplant plant growth using a field experiment method consisting of five dry goat manure dosage treatments: K0 = Control, K1 = 208g/Polybag, K2 = 416g/Polybag, K3 = 624g/Polybag, K4 = 832g/Polybag. The results showed that the K3 treatment had a significant effect on plant height, number of leaves, and stem diameter compared to all other treatments. The novelty of the study lies in the approach of direct use of dry goat manure without a modern fermentation process, which is considered more practical and efficient for local farmers. This finding opens up opportunities for optimizing livestock waste as an environmentally friendly agricultural input, while also addressing agronomic challenges in dry land areas such as Majene. This study recommends the use of dry goat manure as a base fertilizer in horticultural cultivation in dry areas.